A Study on Evacuation Behavior of Evacuees in Case of Utilization of Disaster Information Map - Soo Lee, Ji; Ha Lee, Yoon (International Journal of Engineering and Technology, 2018)
In 2015, the University of Cambridge Centre for Risk Studies measured estimated damages that could be brought about by catastrophes and natural disasters in the following decade and suggested Koreaâ€™s capital, Seoul, was the third most dangerous region among a total of 301 cities around the world. According to the study, the biggest risk factor of Seoul was typhoon, one of natural disasters, and the city could suffer damages worth 44.7 billion dollars over 10 years. Korea, located in the sphere of influence of Northwestern Pacific typhoons, is subject to frequent damages led by summer torrential rains, let alone typhoons. To respond to such disasters, the country is focusing on structural measures such as sewer rehabilitation and installment of drainage pumps and rain detention storages. Those structural measures, however, often become of no use due to poor maintenance or malfunction, and extreme weather events sometimes take place above a predicted range. As there is a need for a discussion on nonstructural measures that employ data on inundation risk, this paper attempts to explore the utilization of disaster information map, one of the most representative nonstructural response measures, and the consequent evacuation behavior presented by evacuees.Â Â